Occurrence of parasites in salads in restaurants in Aparecida de Goiânia, Goiás, Brazil - Veloso Perim, Lucas; Carneiro Canedo Custódio, Natália; de Castro Vieira Lima, Victória; Ataide Silva Lima da Igreja, Jaqueline; de Sousa Mendes Moreira Alves, Daniella; Ribeiro Storchilo, Heloísa; Roberto Gomes Junior, Antonio; Maria de Castro, Ana; Leonardo Guimarães da Costa, Webster; Hallison Alves Rezende, Hanstter (Revista de Patologia Tropical / Journal of Tropical Pathology, 2020)
Parasitoses are the most widespread diseases in the world. They are transmited via contaminated water or food. Considering that the daily consumption of vegetables is estimated at 142g per person, the purpose of this study was to evaluate the occurrence of parasites in salads available for consumption in restaurants in Aparecida de Goiânia, Goiás State. Salad samples were collected from the restaurants and parasitological analysis was performed using the Willis, Hoffman, Faust and Ziehl Neelsen techniques as well as cultures for the isolation of free-living amoebae. 51 samples were analyzed, 16 (31.4%) were positive. The parasites detected were: Acanthamoeba spp. in 12 (23.5%); free-living larvae, Schistosoma mansoni and Entamoeba coli in 1 (2.0%); Endolimax nana in 2 (3.9%). The PCR technique determined that 17.6% of the samples presented Toxoplasma gondii DNA. These techniques evidenced that the salad samples presented parasite contamination not only in the restaurants with the lowest price per Kg, but also in the most expensive ones. Therefore, in addition to effective sanitary surveillance, prophylactic measures are necessary regarding suppliers, handlers and restaurant owners to prevent the spread of these and other parasites. KEY WORDS: Food contamination; food parasitology; polymerase chain reaction.